(untitled) (Economics and region, 2016)
In the article the authors reveal the essence of her patriotism, considering it a higher moral sense of love for the country, for his people, as a socio-economic phenomenon. It emphasized how important it is today among the patriotic education of the school and students. From what this education will have the results, the article says, the future of Ukraine; at that time indicated K. Ushinsky and B. Sukhomlinsky that patriotic education problems associated with the education of young people ready to work actively to improve the socio-economic situation in the country. Noted seems relevant based on the fact that the current socio-economic development of Ukraine indicators are quite low. The article notes that a considerable part of graduates of Ukrainian educational institutions goes to study and then work in other countries, thereby adding not only intelligent, but also the economic potential of the countries to which they go. Particular attention is paid to the fact that in the present circumstances patriotic education should be aimed primarily at children, adolescents and youth. Its main elements should be: create a sense of pride in the achievements of the state; respect for the history, culture, traditions and spiritual values of their people; enthusiasm for the heroic deeds of the past and present; love for mother nature; veneration of customs, rituals; sense of national dignity and the like. The article stresses that the patriotic education in the educational process presupposes the existence of an appropriate educational content, which reflects the assimilation of the fundamentals of science, contributing to the formation of every young person in the course of educational activity the sense of pride in their country. It is noted that the success achieved where there is coordination, linkages and continuity between the basic functioning system of patriotic education, namely: family, preschool institutions, schools and universities; where the structure of the process of patriotic education includes the need to comply with clear goals and objectives, content, patterns and contradictions, principles, methods and forms of its realization, when all elements of the process of patriotic education are interconnected and interdependent.